Examining Facilitating Condition and Social Influence as Determinants of Secondary School Teachers’ Behavioural Intention to Use Mobile Technologies for Instruction - Oluwaseun Funmilola Buraimoh; Charity H. M. Boor; Gboyega Ayodeji Aladesusi (Universitas Pendidikan Indonesia (UPI), 2023)
This study examined the social influence and facilitating condition as determinants of secondary school teachers’ behavioural intention to use mobile technologies for instruction in Kaduna State, Nigeria. The study adopted descriptive research of the survey type to 958 teachers in Kaduna State, Nigeria. The findings indicated there was strong relationship among teachers’ social influence, facilitating condition and behavioral intention to use mobile technologies with ANOVA value of F (2,956) 61.53 p 0.05, F (2,956) 28,786 p 0.05 and F (2,956) 5.152 p 0.05, respectively. The study concluded that teachers' social influence and facilitating conditions influenced their behavioural intention to use mobile technologies for instruction. The implication is that there might be an improvement in teaching and learning at secondary school if mobile technologies are integrated into teaching. The study recommended among others, that secondary school teachers should help themselves by making use of mobile technologies for instructional purposes and shift their focus from using them for fun and entertainment to improving instructional delivery.